Соціально-антропологічні аспекти сучасної української філософії техніки - Чурсінова, Оксана (Видавництво Львівської політехніки, 2014)
Систематизовано соціально-антропологічні підходи, характерних для української філософії техніки. Підкреслюється роль етичних засад розвитку техніки, обґрунтовується необхідність введення моральних критеріїв до самої структури будь-якої технічної діяльності. In the article the author systematises the typical socio-anthropologic approaches of Ukrainian philosophy of technology. The development of technology in the modern world in general, and in Ukraine in particular, raises a number of questions of socio-anthropological character. These issues concern the human nature, the connection of the fundamental principles of social life with the natural environment, the sense of human life, the future of human culture and civilisation. In this context Ukrainian philosophers should consider the development of philosophy of technology as a factor of the self-awareness strengthening adequate to the current threats, a component of non-indifference common to all mankind, a sense of responsibility for the succeeding generations and for the future of the planet that is the only environment of human existence. The purpose of the article is to systematise the socio-anthropologic conceptions of the representatives of Ukrainian philosophy who investigate the technicalization processes in the modern world and try to identify the perspectives of the scientific and technological progress for the future of humanity. The socio-anthropologic aspects of the technological advancement are examined in the works of many native and foreign philosophers of technology. However, the study of this problem is incomplete though the influence of the technosphere on human life and society should be in the spotlight of philosophy of technology. The investigation of the anthropologic and social aspects of modern Ukrainian philosophy of technology shows that the majority of the Ukrainian philosophers use two approaches while solving the problems of the nature of technology and its sources. 1) Science and technology are not independent phenomena but they are rooted in the ontological foundations of human existence and society. 2) Technology and technosphere are relatively independent phenomena and they develop according to their own logic. The research proves that the first approach prevails. In spite of admitting the connection between the technical activity and human existence, the idea of the mismatch between the science and technology advancement and the real needs and values of the human being and society is widely spread among Ukrainian philosophers. Thereby, the representatives of modern Ukrainian philosophy of technology emphasize the need to bring moral criteria into the structure of any technical activity.
Socio-anthropological aspects of modern Ukrainian philosophy of technology
Keywords: науково-технічний прогрес; техніка; технікознавство; технологія; техносфера; феномен техніки; філософія техніки; scientific and technological advancement; technology; technical competence; technosphere; phenomenon of technology; philosophy of technology